2004
DOI: 10.1097/00054725-200411000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying Colonoscopic Features of Ulcerative Colitis Reflect Histologic Inflammation

Abstract: Magnifying colonoscopy is useful for determining the degree of histologic change without biopsy in patients with ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Therefore, the current pit pattern classification system may not be fully applicable in cases of UC. The pit pattern of the regenerative hyperplastic villous mucosa in UC is difficult to distinguish from neoplastic pit patterns because the pits characteristic of UC can become elongated or irregular, depending on the degree of inflammation 26. We have reported instead that discovery of a high residual density of pits and irregular pit margins upon magnification after indigo carmine dye spraying is useful for differentiating between colitis-associated neoplastic and non-neoplastic lesions 21.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the current pit pattern classification system may not be fully applicable in cases of UC. The pit pattern of the regenerative hyperplastic villous mucosa in UC is difficult to distinguish from neoplastic pit patterns because the pits characteristic of UC can become elongated or irregular, depending on the degree of inflammation 26. We have reported instead that discovery of a high residual density of pits and irregular pit margins upon magnification after indigo carmine dye spraying is useful for differentiating between colitis-associated neoplastic and non-neoplastic lesions 21.…”
Section: Discussionmentioning
confidence: 97%
“…Surface pit pattern classification with ME is known to have a good association with the histopathological diagnosis of colorectal tumor [18]. Similarly, recent studies have shown that ME findings are significantly correlated with histological grades [27, 28]. Of note, it is reported that ME could be useful in assessing microscopic inflammatory features of UC that cannot be determined by white light colonoscopic examination [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent studies have shown that ME findings are significantly correlated with histological grades [27, 28]. Of note, it is reported that ME could be useful in assessing microscopic inflammatory features of UC that cannot be determined by white light colonoscopic examination [27, 28]. The use of ME in UC is relatively new and different ME classifications have been proposed to date [18, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these studies the groups in active and remission phases that were detected by colonoscopy were mixed. Kunihiro et al 35 also reported the correlation between histological and magnifying colonoscopy findings. However, that report only described the magnifying colonoscopy findings of UC from an active stage to a remission stage.…”
Section: Histological Findingsmentioning
confidence: 92%